Russian nurses’ readiness for transcultural care of palliative patients - Nataliya Kasimovskaya; Natalia Geraskina; Elena Fomina; Svetlana Ivleva; Maria Krivetskaya; Nina Ulianova; Marina Zhosan (BMC Palliative Care, 2023)
Abstract Palliative care involves an approach aimed at improving the quality of life of patients and their families, who are forced to cope with the problems associated with life-threatening diseases. This definition includes a growing group of patients around the world. It requires an extension of the definition of patients in need of palliative care in countries such as Russia and a significant improvement in the work of nursing personnel with these patients. This study aims to determine the level of preparedness of nursing personnel for specialized care (transcultural care) and the quality of care provided to palliative patients. The presented findings of the study demonstrate the relevance of developing transcultural competence, which enables significant improvement in the quality of life of palliative patients. The analysis of medical workers’ assessment of the level of specific training and their intercultural preparedness was conducted based on hospices (Moscow). A survey was conducted among 113 medical workers of the middle level of education aged between 28 and 56 (average of 44.2 years) and experience in palliative care ranged from 3 to 18 years (average of 9.5 years). The Intercultural Readiness Check (IRC) test, widely used to assess nursing staff worldwide, was used for the survey to determine the level of readiness for transcultural care. A strong correlation was found between a number of the test scales and measures of participants’ age and experience. The presented material demonstrates the realization of an interdisciplinary approach to the issues of specific training of nursing personnel in the field of “transcultural care” in providing palliative care to incurable patients.